2022
DOI: 10.3389/fnut.2022.930176
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D for Recovery of COVID-19 in Patients With Chronic Kidney Disease

Abstract: The severity of coronavirus disease 2019 (COVID-19) is determined not only by viral damage to cells but also by the immune reaction in the host. In addition to therapeutic interventions that target the viral infection, immunoregulation may be helpful in the management of COVID-19. Vitamin D exerts effects on both innate and adaptive immunity and subsequently modulates immune responses to bacteria and viruses. Patients with chronic kidney disease (CKD) frequently have vitamin D deficiency and increased suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…Vitamin D deficiency is seen in most patients suffering from CKD; its deficiency can affect the COVID-19 outcome. Vitamin D influences innate and adaptive immunity, which influences how the immune system reacts to viruses and bacteria [ 198 ]. According to previous research, even a short-term acute vitamin D shortage can cause hypertension and affect the parts of the renin-angiotensin system that cause kidney damage.…”
Section: Therapeutic Management Of Renal Disorder Patients With Covid-19mentioning
confidence: 99%
“…Vitamin D deficiency is seen in most patients suffering from CKD; its deficiency can affect the COVID-19 outcome. Vitamin D influences innate and adaptive immunity, which influences how the immune system reacts to viruses and bacteria [ 198 ]. According to previous research, even a short-term acute vitamin D shortage can cause hypertension and affect the parts of the renin-angiotensin system that cause kidney damage.…”
Section: Therapeutic Management Of Renal Disorder Patients With Covid-19mentioning
confidence: 99%
“…Vitamin D has been reported to protect against infectious diseases, including SARS-CoV-2 infection [11]. Recent studies have reported that lower serum 25-hydroxyvitamin D (25OHD) level is a risk factor for severity and mortality in COVID-19 [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…6 Many studies suggested an association between vitamin D deficiency and clinical outcomes of covid-19 infection, while others failed to document such a relation. 7 Other studies investigated the role of vitamin D supplementation on infection severity and outcome. 8,9 The present study aimed to evaluate the clinical and prognostic significance of baseline vitamin D levels in hospitalized Egyptian covid-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies suggested an association between vitamin D deficiency and clinical outcomes of covid-19 infection, while others failed to document such a relation. 7 Other studies investigated the role of vitamin D supplementation on infection severity and outcome. 8 , 9 …”
Section: Introductionmentioning
confidence: 99%